Evaluating the Challenges and Prospects of Fuel Subsidy Removal on Nigeria’s Economy - Mohammed, Ahmed; Yusuf, Afeez Ayo; Mele, Ibrahim Bukar; Yahaya, Haruna; Olowo-Oribi, Fatimoh Aderoju (Kashere Journal of Politics and International Relations, 2024)
Nigeria’s fuel subsidy program has been a contentious issue for decades. While intended to benefit citizens, its implementation has faced challenges like corruption and fiscal burden. This paper examines the potential outcomes of fuel subsidy removal, focusing on both the difficulties it presents and the economic opportunities it creates. The paper used secondary data such as books, journals, newspapers and magazines, and content analysis as its methodology. Neo-liberalism was adopted as the possible framework that guide the study. Neo-liberalism is a policy model that encompasses both politics and economics. It is a political and economic philosophy that emphasizes free trade, deregulation, globalization and a reduction in government spending. The Findings discovered some challenges of fuel subsidy removal which includes: increased cost of living, potential social unrest, high transportation cost and the impact on vulnerable populations. It then investigates the potential benefits, such as reduced government spending, improved productivity in the oil sector, increased revenue generation, alleviate fuel theft, adequate resources, reduces government borrowing, increased investment in other critical sectors like infrastructure, and a more efficient fuel market. The paper recommends that the Federal government should fast track the rehabilitation of refineries, enforce new national minimum wage in all the sectors including private sector and introduce subsidy in transportation sector as against temporary palliatives introduced by the federal government to cushion the effects of fuel subsidy removal.